2019
DOI: 10.5194/acp-19-10591-2019
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results from the FARCE 2015 campaign: multidisciplinary study of the forest–gas–aerosol–cloud system on the tropical island of La Réunion

Abstract: Abstract. The Forests gAses aeRosols Clouds Exploratory (FARCE) campaign was conducted in March–April 2015 on the tropical island of La Réunion. For the first time, several scientific teams from different disciplines collaborated to provide reference measurements and characterization of La Réunion vegetation, volatile organic compounds (VOCs), biogenic VOCs (BVOCs), (bio)aerosols and composition of clouds, with a strong focus on the Maïdo mountain slope area. The main observations obtained during this 2-month … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 110 publications
5
49
1
Order By: Relevance
“…The ER can be computed from the EF by taking the molecular weights (MWs) of both species into B. Verreyken et al: African biomass burning plumes over the south-west Indian Ocean Table 1. In situ routine observations at RUN and their respective limits of detection (LoDs) and statistical uncertainties (σ ) (Zhou et al, 2018;Duflot et al, 2019 xylenes a (C 8 H 10 ) 10 Y 7 137 sum of monoterpenes a (C 10 H 16 ) 10 Y 8…”
Section: Enhancement Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…The ER can be computed from the EF by taking the molecular weights (MWs) of both species into B. Verreyken et al: African biomass burning plumes over the south-west Indian Ocean Table 1. In situ routine observations at RUN and their respective limits of detection (LoDs) and statistical uncertainties (σ ) (Zhou et al, 2018;Duflot et al, 2019 xylenes a (C 8 H 10 ) 10 Y 7 137 sum of monoterpenes a (C 10 H 16 ) 10 Y 8…”
Section: Enhancement Ratiosmentioning
confidence: 99%
“…Photochemical degradation and dry and wet deposition are the major sink processes. Global OVOC budgets are still prone to large uncertainties due to an incomplete understanding of direct emissions, photochemical production and loss processes, oceanatmosphere exchange (Millet et al, 2010;Fischer et al, 2012;Read et al, 2012;Wang et al, 2019), and a paucity of (O)VOC data, especially in remote marine areas where the oxidative capacity of the atmosphere is mainly controlled by OVOCs in comparison to all other NMVOCs (Lewis et al, 2005;Carpenter and Nightingale, 2015;Travis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ routine observations at RUN and their respective limits of detection (LoD) and statistical uncertainties (σ). (Zhou et al, 2018;Duflot et al, 2019 xylenes α (C8H10) 10 Y 7 sum of monoterpenes α (C10H16) 10 Y 8…”
Section: A2 Austral Winter Variation Of In Situ Measurements At Runmentioning
confidence: 99%
“…A summary of routine measurements from the observatory used in this study is shown in Table 1. A detailed description of these and other operational routine instruments at the observatory can be found in Duflot et al (2019); Baray et al (2013) and Zhou et al (2018).…”
Section: Introductionmentioning
confidence: 99%